Treatment response measurements and survival outcomes in a cohort of newly diagnosed AL amyloidosis. (3rd July 2021) - Jimenez-Zepeda, Victor H.; Lee, Holly; McCulloch, Sylvia; Tay, Jason; Duggan, Peter; Neri, Paola; Bahlis, Nizar
Abstract: Introduction: The assessment of AL amyloidosis response is based on serum free light chains (sFLC) levels, and serum and urine monoclonal protein investigations. Recently, difference between involved and uninvolved free light chains (dFLC), involved free light chain (iFLC) and complete response (CR) has been reported as independent predictor of survival and a refinement of the hematological response criteria has been proposed by several groups. Methods: In the current study, all consecutive newly diagnosed symptomatic AL amyloidosis patients were evaluated. The primary objective of the study was to assess hematological and organ response after first line of treatment. Results: A cohort of 76 cases with upfront treatment was used for this analysis. After a median of 3 months post-therapy, hematological response was seen in 88% of cases including CR in 26.3%, VGPR in 38.2% and PR in 23.7%. Median OS was longer in patients with dFLC < 10 mg/L at 3 months, iFLC <20 mg/L at 1 and 3 months, and those achieving CR. Multivariate analysis showed presence of CR as the most important independent prognostic factors for survival. Conclusions: Our study suggests that maximal sFLC response and CR are potential endpoints to define clinical outcomes. Large collaborative studies are required to validate and optimize response criteria.